UNCONDITIONAL PROPERTIES OF ESTIMATORS OF REPEATED MEASUREMENTS MODEL - Hayder Abbood Kori; Abdulhussein Saber AL-Mouel (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
We have four types of estimators of repeated measurements model and obtained these estimators by maximum likelihood method (MLM), restricted maximum likelihood method (REMLM) and modified restricted maximum likelihood method (MREMLM)(see [8] and [9]). In this paper, we study the unconditional properties of the repeated measures model of the four unbiased types.